Generalized pustular psoriasis in a toddler with IL36RN mutation: a case report - Adi, Ghaith; Shaath, Mohammed Rami; Adi, Kareem; Obaid, Zaki; Aldosari, Egab; AlKateb, Faten Ahmed (Frontiers in Immunology, 2024)
Generalized Pustular Psoriasis (GPP) is a dermatological autoinflammatory disease that rarely occurs in children and is associated with complex genetic factors. GPP pathogenesis has been associated with mutations in IL36RN gene, which encodes an interleukin-36 receptor antagonist. GPP usually occurs without a history of psoriasis in the patients or their family members. This case report describes the clinical course of a 3-year-old toddler with GPP. The diagnosis of GPP was confirmed through a comprehensive series of examinations, and genetic testing revealed an IL36RN mutation, providing further insight into the genetic basis of the condition. This case highlights the importance of a genetic perspective for diagnosing GPP, particularly in children.